Simultaneous evaluation of substrate‐dependent CYP3A inhibition using a CYP3A probe substrates cocktail. (September 2016) - Lee, Eunyoung; Shon, Jong Cheol; Liu, Kwang‐Hyeon
Abstract: Cytochrome P450 (P450) 3A (CYP3A) is an enzyme responsible for the metabolism of therapeutic drugs such as midazolam, nifedipine, testosterone and triazolam. It is involved in 40% of all cases of P450‐mediated metabolism of marketed drugs. Therefore, it is important to evaluate the CYP3A‐mediated drug interaction potential of new chemical entities (NCEs). In the past, one P450 isoform‐specific probe substrate has been used at a time to evaluate the degree of inhibition of P450 isoforms by using liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). However, CYP3A enzymes have been shown to have a multi‐substrate binding site. Therefore, multiple CYP3A substrates should be used to evaluate precisely the drug interaction potential of NCEs with the enzyme CYP3A. In this study, a method of screening NCEs for their potential to inhibit by CYP3A enzyme activity was developed. It involves the employment of a CYP3A substrate cocktail (including midazolam, testosterone and nifedipine). The concentration of each CYP3A probe substrate in vitro was optimized (0.1 μm for midazolam, 2 μm for testosterone and 2 μm for nifedipine) to minimize mutual drug interactions among probe substrates. The method was validated by comparing inhibition data obtained from the incubation of CYP3A with each individual substrate with data from incubation with a cocktail of all three substrates. The CYP3A inhibition profiles from the substrate cocktail approach were similar to those from the individual substrates approach. This new method could be an effective tool for the robust and accurate screening of the CYP3A inhibition potential of NCEs in drug discovery. Copyright © 2016 John Wiley & Sons, Ltd.